An LRR-only protein representing a new type of pattern recognition receptor in Chlamys farreri. Issue 1 (January 2016) - Wang, Mengqiang; Wang, Lingling; Guo, Ying; Yi, Qilin; Song, Linsheng
Abstract: Accumulating evidence has demonstrated that leucine-rich repeat (LRR)-only proteins could mediate protein-ligand and protein–protein interactions and were involved in the immune response. In the present study, an LRR-only protein (designed as Cf LRRop-1) was cloned from Zhikong scallop Chlamys farreri . The complete cDNA sequence of Cf LRRop-1 contained an open reading frame (ORF) of 1377 bp, which encoded a protein of 458 amino acids. An LRRNT motif, an LRR_7 motif and seven LRR motifs were found in the deduced amino acid sequence of Cf LRRop-1. And these seven LRR motifs contained a conserved signature sequence LxxLxLxxNxL. The mRNA transcripts of Cf LRRop-1 were constitutively expressed in all the tested tissues, including haemocytes, muscle, mantle, gill, hepatopancreas and gonad, with the highest expression level in hepatopancreas. After the stimulation of lipopolysaccharide (LPS), peptidoglycan (PGN), glucan (GLU) and polyinosinic-polycytidylic acid (poly I:C), the mRNA transcripts of Cf LRRop-1 in haemocytes all increased firstly within the first 6 h and secondly during 12–24 h post stimulation. The mRNA expression level of Cf LRRop-1 was continuously up-regulated, after the expression of Cf TLR (previously identified Toll-like receptor in C . farreri ) was suppressed via RNA interference (RNAi). The recombinant Cf LRRop-1 protein could directly bind LPS, PGN, GLU and poly I:C, and induce the release of TNF-α in mixed primary cultured scallop haemocytes. These results collectively indicated that Cf LRRop-1 would function as a powerful pattern recognition receptor (PRR) and play a pivotal role in the immune response of scallops. Highlights: An LRR-only protein gene was cloned from scallop Chlamys farreri . Its mRNA transcripts in haemocytes increased after PAMP stimulations. Cf LRRop-1 exhibited binding activity to various PAMPs. The mRNA expression level of Cf LRRop-1 was up-regulated when Cf TLR was suppressed. Cf LRRop-1 induced release of TNF-α from mixed primary cultured scallop haemocytes.